Survey of perceived stress-inducing problems among dental students, Saudi Arabia - Samar A. Al-Saleh; Ebtissam M. Al-Madi; Nadia S. Al-Angari; Huda A. Al-Shehri; Mohammed Mohammed Shukri (Elsevier, 2010)
Objective: This study was conducted to assess the problems related to stress encountered by Saudi dental students. Methods: One thousand and thirty questionnaires were distributed in four dental schools to all students from 2nd year level up to the internship level. The questionnaire contained 66 items organized into four categories: personal and administrative, theoretical, preclinical and clinical. The relationship between the demographic variables and students' academic performance with the investigated items was also assessed. Results: The response rate was 53%. Saudi dental students showed high levels of perceived stress. The clinical training issues imposed the highest level of stress on the students. Some significant relationships between the investigated variables and the level of the perceived stress were found. Conclusions: Female students had higher mean overall problem scores compared to male students, and second-year students showed lower perceived problems compared to other students. Keywords: Stress, Dental students, Education, Clinical training